Individual-level characteristics associated with oral HIV test acceptability among Peruvian men who have sex with men and transgender women: A cross-sectional study - Flores, Juan A (2018)
Objectives Peruvian men who have sex with men (MSM) and transgender women (TGW) are highly vulnerable to HIV infection (HIV), but stigma, access issues and fear of venipuncture hamper testing. The oral HIV test - which uses oral fluids and provides results in 20 minutes - could reduce these barriers. The objective of this study was to determine the acceptability of the oral HIV test and the individual-level factors associated with its acceptability among MSM and TGW. Methods We conducted a cross-sectional secondary analysis among Peruvian MSM and TGW attending a community-based health centre between February 2012 and February 2013 to determine the individual-level factors associated with oral HIV test acceptability. Results Of 334 participants, 88% were MSM and 12% TGW. Overall, 85% of participants indicated their acceptability of the oral HIV test. Acceptability was higher in MSM than TGW (85.7% vs 80.0%) but this difference was not significant. Factors associated with acceptability in MSM were: tertiary or higher education (prevalence ratio (PR)=1.18, 95% CI 1.06 to 1.32 and PR=1.16, 95% CI 1.03 to 1.30, respectively); sex with drug use (PR=1.19, 95% CI 1.05 to 1.36); believing that HIV is transmitted by saliva (PR=1.20, 95% CI 1.08 to 1.33); and potential use of the oral test at home (PR=1.56, 95% CI 1.32 to 1.85). The only factor associated with lower acceptability was having had first anal intercourse between 14 and 19 years of age (PR=0.89, 95% CI 0.80 to 0.98). Conclusions We identified the individual factors associated with oral HIV test acceptability among Peruvian MSM and TGW. Expanded use of the oral HIV test to increase testing rates among Peruvian MSM and TGW is recommended. Trial registration number NCT01387412, post-results. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018. All rights reserved. No commercial use is permitted unless otherwise expressly granted.